The future of circulating tumor DNA as a biomarker in HPV related oropharyngeal squamous cell carcinoma. (March 2022) - Haring, Catherine T.; Dermody, Sarah M.; Yalamanchi, Pratyusha; Kang, Stephen Y.; Old, Matthew O.; Chad Brenner, J.; Spector, Matthew E.; Rocco, James W.
Highlights: Human papillomavirus (HPV) circulating tumor (ct) DNA has emerged as a liquid biomarker in oropharyngeal cancer. CtDNA levels correspond to disease burden and are associated with treatment response and disease recurrence. Opportunities exist for rigorous validation and improved techniques to detect ctDNA. Improved detection of ctDNA would allow for individualized treatment paradigms and population level screening. The economic value of using ctDNA in head and neck cancer care remains understudied. Abstract: Human papillomavirus (HPV) related oropharyngeal squamous cell carcinoma (OPSCC) is associated with improved outcomes compared to non-virally mediated disease. Clinical trials are actively investigating de-escalation strategies to maintain excellent survival outcomes while minimizing toxicity. Delivery of effective precision medicine-based therapeutic approaches are strengthened by the identification of biomarkers to predict treatment response. Plasma circulating tumor (ct) DNA is the most studied liquid biomarker in head and neck cancer and has shown great promise in the ability to determine treatment response and monitor for disease recurrence. In this review, we examine the emerging evidence for ctDNA as a biomarker in HPV related OPSCC and discuss opportunities for future investigation and integration into clinical practice.